Valuation of Ecosystem Services in Protected Areas: The Case of the Abisko National Park (Sweden) - Nikodinoska, Natasha; Paletto, Alessandro; Franzese, Pier Paolo; Jonasson, Christer (Journal of Environmental Accounting and Management, 2026)
Sub-Artic ecosystems have evolved and adapted to extreme environmental condition. Yet, these ecosystems are vulnerable to local and global impacts due to human activities and climate change. In addition, a controversial debate over land use in the Swedish Lapland is still open, involving different stakeholders’ interests and activities. The Abisko National Park (Swedish sub-Arctic Lapland) is one of the Europe’s largest remaining wilderness areas and an important tourist attraction. In this study, an economic valuation of the main ecosystem services (ES) was performed by using the Contingent Valuation (CV) method. The categories of ES generated in the Park were identified and tourists were chosen as main stakeholders in the area. Tourists were then interviewed about their perception on ES and their willingness to pay (WTP) for supporting conservation activities capable of preserving the functionality of the Park to provide different goods and services. Results show that 61% of the respondents were willing to pay for the implementation of adaptation strategies coping with climate change impact. The mean individual WTP were found to be 6.20 € for the provisioning services, 5.69 € for the regulating services, 6.35 € for supporting services, 4.09 € for cultural services, while the total mean WTP per tourist was found to be 22.33 €. In addition, statistically significant correlations between tourists’ perceptions and individual WTP for three ES categories were found. These outcomes could support local decision makers in charge for the implementation of climate change adaptation strategies in the Park. However, it is important to remark that for a more comprehensive assessment of ecosystem services and their role in support of human well-being, the economic valuation should be integrated by a solid biophysical accounting.